Electromyography study of the lumbar iliocostal and maximum gluteus muscles during locomotion - Bankoff, A. D. P.; de Moraes, A. C.; Fonseca Neto, D. R.; Gassi, E. R.; Okano, A. H. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction In recent years the electromyography has been greatly emphasized in sport medicine with much research being done in muscular neuro-biomechanics. Many investigations were conducted in different sports such as swimming [1], gymnastic [2], bodybuilding [7], cycling [5], artistic gymnastics [6], Roman table [3], and soccer [4]. However, very few studies analyzed the muscular behavior during locomotion in diverse aspects. Based in these previous studies analyzed the muscular behavior of the lumbar iliocostal and gluteus maximus muscles during locomotion on the ground and on a treadmill. Methods The muscles were monitored using the electromyography in 10 male individuals (ages 19 to 25 years old). The objective was to study the muscles´action potential during locomotion on the ground as well as on a treadmill. During ground locomotion the individual had to prepare himself running in place for 15 seconds after which he ran at top speed for 10 meters. For the treadmill test, the Bruce protocol was used: 7th stage, at 6 mph, with 22% of inclination, for 60 seconds. However, electromyography readings presented here were taken during the last 5 seconds of the treadmill test. Results The results showed significant differences between the situations (treadmill and ground) as well as differences between gluteus maximus and lumbar iliocostal muscles in the same situation